Mutant IDH1 inhibits PI3K/Akt signaling in human glioma - Birner, Peter; Pusch, Stefan; Christov, Christo; Mihaylova, Stiliana; Toumangelova‐Uzeir, Kalina; Natchev, Sevdalin; Schoppmann, Sebastian F.; Tchorbanov, Andrey; Streubel, Berthold; Tüttenberg, Jochen; Guentchev, Marin (Cancer, 2014)
BACKGROUND Recently, isocitrate dehydrogenase 1 (IDH1) was identified as a major participant in glioma pathogenesis. At present, the enzymatic activity of the protein has been the main topic in investigating its physiological function, but its signaling pathway allocation was unsuccessful. Interestingly, proteins regulated by phosphoinositide 3-kinase (PI3K)/Akt signaling, are among the top downregulated genes in gliomas associated with high percentage of IDH1 and IDH2 mutations. The aim of this study was to investigate a hypothetical relation between IDH1 and PI3K signaling. METHODS The presence of mutant IDH1 and markers for active PI3K/Akt signaling, present as phosphorylated Akt and podoplanin (PDPN), were investigated in a discovery cohort of 354 patients with glioma. In vitro experiments were used to confirm functional links. RESULTS This study shows an inverse correlation between mutant IDH1 and markers for active PI3K/Akt signaling. In support of a functional link between these molecules, in vitro expression of mutant IDH1 inhibited Akt phosphorylation in a 2-hydroxyglutarate-dependent manner. CONCLUSIONS This study provides patient tumor and in vitro evidence suggesting that mutant IDH1 inhibits PI3K/Akt signaling. Cancer 2014;120:2440-2447. © 2014 American Cancer Society.